Newtonian to non-newtonian fluid transition of a model transient network. Issue 17 (25th April 2018) - Nava, Giovanni; Yang, Tie; Vitali, Valerio; Minzioni, Paolo; Cristiani, Ilaria; Bragheri, Francesca; Osellame, Roberto; Bethge, Lucas; Klussmann, Sven; Paraboschi, Elvezia Maria; Asselta, Rosanna; Bellini, Tommaso
Abstract : By using a model DNA hydrogel we show that the onset of non-Newtonian behavior can be fully understood on the basis of the connectivity of the network and the bond energy. Abstract : The viscosity of gel-forming fluids is notoriously complex and its study can benefit from new model systems that enable a detailed control of the network features. Here we use a novel and simple microfluidic-based active microrheology approach to study the transition from Newtonian to non-Newtonian behavior in a DNA hydrogel whose structure, connectivity, density of bonds, bond energy and kinetics are strongly temperature dependent and well known. In a temperature range of 15 °C, the system reversibly and continuously transforms from a Newtonian dispersion of low-valence nanocolloids into a strongly shear-thinning fluid, passing through a set of intermediate states where it behaves as a power-law fluid. We demonstrate that the knowledge of network topology and bond free energy enables to quantitatively predict the observed behavior using established rheology models.